WNK1, a Novel Mammalian Serine/Threonine Protein Kinase Lacking the Catalytic Lysine in Subdomain II - Bing-e Xu; Jessie M. English; Julie L. Wilsbacher; Steve Stippec; Elizabeth J. Goldsmith; Melanie H. Cobb (2000)
We have cloned and characterized a novel mammalian serine/threonine protein kinase WNK1 (withno lysine (K)) from a rat brain cDNA library. WNK1 has 2126 amino acids and can be detected as a protein of ∼230 kDa in various cell lines and rat tissues. WNK1 contains a small N-terminal domain followed by the kinase domain and a long C-terminal tail. The WNK1 kinase domain has the greatest similarity to the MEKK protein kinase family. However, overexpression of WNK1 in HEK293 cells exerts no detectable effect on the activity of known, co-transfected mitogen-activated protein kinases, suggesting that it belongs to a distinct pathway. WNK1 phosphorylates the exogenous substrate myelin basic protein as well as itself mostly on serine residues, confirming that it is a serine/threonine protein kinase. The demonstration of activity was striking because WNK1, and its homologs in other organisms lack the invariant catalytic lysine in subdomain II of protein kinases that is crucial for binding to ATP. A model of WNK1 using the structure of cAMP-dependent protein kinase suggests that lysine 233 in kinase subdomain I may provide this function. Mutation of this lysine residue to methionine eliminates WNK1 activity, consistent with the conclusion that it is required for catalysis. This distinct organization of catalytic residues indicates that WNK1 belongs to a novel family of serine/threonine protein kinases.